Genetic Susceptibility to Thirdhand-Smoke-Induced Lung Cancer Development. Issue 9 (16th June 2018) - Hang, Bo; Mao, Jian-Hua; Snijders, Antoine M
Abstract: : Recently, potential health concerns have been raised about thirdhand smoke (THS), a much less well-understood type of smoke exposure defined as residual tobacco smoke sorbed onto indoor surfaces after active smoking has ceased. THS exposure is derived from the involuntary inhalation, ingestion, or dermal uptake of indoor pollutants. The timescale for exposure to THS pollution is generally much longer than secondhand smoke, and could stretch to days, months, or years (long-term, low-level exposure). Recent studies showed that exposure to THS at early age in mice can affect body weight, immunity, and lung cancer development. However, adverse health effects of THS in human populations remain poorly understood and many questions remain unanswered. One major question is how genetic factors influence susceptibility to THS-induced health effects, especially tumor development and whether there is an age-specific window of susceptibility for these effects. By addressing these questions, we will provide a better understanding of the effects of THS on human health and disease. This information would address critical knowledge gaps that are required for the formulation of policies related to indoor air quality. Implications: THS, the residual tobacco smoke remaining in the environment after tobacco has been smoked, represents an underestimated public health hazard. Evidence supports its widespread presence in indoor environments. Vulnerable populations are believed to include infants and children living in a smoking household exposed to THS and/or secondhand smoke, and exposure has been identified as a risk factor for lung cancer later in life. These and future studies will provide novel and important evidence of how early-life exposure to THS affects cancer development and other diseases, which should be useful for framing and enforcing new policies against passive smoking in the world.